Pengaruh Gaya Hidup, Kemudahan dan Kepercayaan Terhadap Perilaku Konsumtif Generasi Z Muslim Pengguna SPay Later - Rosyada, Mohammad (Coopetition : Jurnal Ilmiah Manajemen, 2024)
This research aims to determine the influence of lifestyle, ease of use of PayLater services, and trust in using the PayLater application on the consumer behavior of generation Z Muslims who use SPayLater. This research is quantitative research with the data source for this research referring to primary data originating from generation Z Muslims who use SPayLater in Pekalongan City. The sampling technique uses purposive sampling with a sample size of 100 people and the data analysis method uses multiple linear regression analysis. The results of this research show that Lifestyle, Convenience and Trust partially have a positive and significant effect on the consumer behavior of generation Z Muslims who use SPayLater. Apart from that, lifestyle, convenience and trust simultaneously influence the consumer behavior of generation Z Muslims who use SPayLater. The Adjusted R Square value of 0.229 shows that the 22.9% increase in consumer behavior of generation Z Muslims using SPayLater in Pekalongan City can be explained by the independent variables, namely Lifestyle, Convenience and Trust. Meanwhile, the remaining 77.1% is explained by other variables not examined in this research.